Analysis of Supply Control of Soybean Raw Materials in Tempe Products Using The EOQ (Economic Order Quantity) Method - Ramadan Ramadan; La Rianda; Rosmawaty Rosmawaty (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2022)
This study aims to analyze the inventory control of soybean raw materials in tempeh products using the EOQ (Economic Order Quantity) method in Jaya Satu Home Industry, Konda District, Konawe Selatan Regency. The determination of the research location was carried out purposefully. Data collection was carried out through observation, interview, and documentation methods. The analytical method used is EOQ (Economic Order Quantity). The results showed that the minimum order quantity of rice (economic order quantity) in month 1 was 6.73 tons and continued to increase monthly.In contrast, in the 12th month, the minimum order was 7.83 tons. The safety stock in month 1 of 2023 is 1,210 kg/week and continues to increase until month 12, when the safety stock of soybean raw materials is 1,404 kg/week. The maximum inventory in the 1st month of the year is 7.94 tons and continues to increase every month, whereas, in the 12th month, it is 9.23 tons. The number of reorder points in the 1st month was 2.94 tons and continued to increase every month, whereas, in the 12th month, it was 3.41 tons.